Case report: Intraosseous hemangioma of the lateral clavicle treated by surgical resection and reconstructed by three-dimensional-printed personalized prosthesis - Li, Zhuangzhuang; Zou, Chang; Lu, Minxun; Zhang, Yuqi; Gong, Taojun; Wang, Jie; Luo, Yi; Zhou, Yong; Min, Li; Tu, Chongqi (Frontiers in Bioengineering and Biotechnology, 2023)
Background: Intraosseous hemangiomas occurring the clavicle is uncommon. Reconstruction of the clavicle is suggested to maintain the normal shoulder joint function and prevent adverse outcomes. Complex anatomy shape of the clavicle remains a great challenge for prosthetic reconstruction of the clavicle. Case presentation: A 37-year-old female with no conclusive history of trauma presented with progressive mass at the right lateral clavicle for five years. The patient was treated by surgical resection and reconstructed by three-dimensional printed personalized prosthesis. Postoperatively radiographic examinations revealed a good position of the prosthesis, neither breakage nor loosening was detected (Figure 6). The right shoulder mobility returned to approximate level of preoperative shoulder 2 months after surgical reconstruction, with the range of motion (ROM) of flexion 80 degrees, extension 40 degrees, abduction 80 degrees, adduction 30 degrees, external rotation 55 degrees, and internal rotation 60 degrees. The patient maintained the normal shoulder function during the 48 months follow-up period. There was no pain during shoulder motion. The Musculoskeletal Tumor Society Score (MSTS) score was 29 and the Functional Evaluation Form recommended by the American Shoulder and Elbow Surgeons (ASES) score was 95. Conclusion: 3D-printed personalized prosthesis is a good option to reconstruct the lateral clavicle bone defect and restore the shoulder support structure. It maintains the normal shoulder joint function and avoids adverse effects on daily activities after claviculectomy.